Correlation of Tumor Vascularization Using Spectral Pulse Wave Doppler with Neoadjuvant Chemotherapy Response in IB2 and IIA2 stages of Cervical Cancer - Muhammad, Syamel; Rahmadita, Nindya (Andalas Obstetrics And Gynecology Journal, 2020)
Cervical cancer is an abnormal growth or cell changes in the cervical wall, which is the 4th rank in the most common cancer among female and the 2nd most common cancer in female aged fifteen until fourty four years old worldwide. Neovascularization becomes an important step in determining the onset and progressive cancer. Neoadjuvant chemotherapy has been evaluated as a treatment strategy in the stages IB2 and IIA2. The use of chemotherapy drug becomes more effective in adjacent and regular vascularization, and it allows the blood flow to the organs more quickly. This study aims to determine the correlation of tumor vascularization using Spectral Pulse Wave Doppler with neoadjuvant chemotherapy response in IB2 and IIA2 stages of cervical cancer. This research is a cohort analytic study which involves thirty six of patient in IB2 and IIA2 stages. The sampling is selected by using consecutive sampling technique. The data includes the result of ultrasound examination and were analyzed by using the Chi-square test. The results of the research on good and poor tumor vascularization had a good response to thirty of patient (83.3%) who were given neoadjuvant chemotherapy. There was no significant effect between tumor vascularization using Spectral Pulse Wave Doppler to the responses of neoadjuvant chemotherapy in IB2 and IIA2 stages of cervical cancer.Keywords: tumor vascularization using Spectral Pulse Wave Doppler, responses of neoadjuvant chemotherapy, IB2 and IIA2 stages of cervical cancer